MODEL PENGABDIAN MASYARAKAT: MENINGKATKAN KEMAMPUAN LITERASI WARGA RUTAN MELALUI PEMBELAJARAN BERBASIS PERMAINAN - Hertanti, Alfiramita; Aprisal, Aprisal (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2025)
This activity is a community service carried out in Rutan Kelas IIB Kab. Majene. The main purpose of this activity is to build awareness and improve the literacy skills of the detainees of Rutan Kelas IIB Kab. Majene. This activity not only focuses on improving the reading and writing skills of detainees, but also educates the importance of having good reading and writing skills. This program is implemented by implementing game-based learning. Learning is also carried out with technological media using the wordwall application. This program reflects that improving reading and writing literacy is the right of all levels of society, including those who are still undergoing detention in Rutan Kelas IIB Kab. Majene.